EARLY PALEOZOIC AGE AND GEODYNAMIC SETTING OF THE BOTOGOL AND KHUSHAGOL ALKALINE MASSIFS IN THE CENTRAL ASIAN FOLDBELT - Nikiforov A.V.; Yarmolyuk V.V. (My University, 2007)
The Altai–Sayan foldbelt, the southwestern sector of the Early Caledonian framework of the Siberian Platform, includes abundant magmatic complexes with alkaline rocks (alkaline gabbroids, nepheline syenites, alkaline syenites, granites, and their volcanic analogues) that are indicators of within-plate magmatism in the region. On the basis of K–Ar studies, these rocks were traditionally attributed to Devonian rifting. However, recent Rb–Sr and Sm–Nd data showed that alkaline magmatism also occurred here at earlier stages. However, the number of these datings is obviously insufficient to reconstruct reliably the geodynamic model of the formation of Caledonides in the Central Asian foldbelt (CAFB).
Keywords: Paleozoic; Paleozoic::Cambrian; Палеозой::Кембрийская